The Impact of China’s Low-Carbon Initiative on the Location Expansion of International SPA Enterprises - Zhaoyang Zhao; Chong Ye (Discrete Dynamics in Nature and Society)
“Fast fashion” represents a short product life cycle, and international SPA enterprises are therefore criticised as representatives of high energy consumption, pollution, and emissions, which is contrary to China’s goal of achieving carbon neutrality. In the context of China’s shift to a low-carbon economic development model, how should SPA enterprises breakthrough in the face of China’s large-scale market advantage and domestic demand potential? Based on the statistics of 277 prefecture-level cities from 2010 to 2018, this article selects 5 leading international SPA enterprises and uses the difference-in-differences (DID) method to explore the impact of low-carbon initiative on the location expansion of international SPA enterprises. The results suggest that the quantity of location expansions of SPA enterprises in the pilot cities is significantly lower by approximately 0.418 units compared with the nonpilot cities, implying that the low-carbon initiative has a significant inhibitory effect on the location expansion of SPA enterprises. After a series of robustness tests, the conclusion is valid. The results of the heterogeneity test suggest that the suppression effect is mainly found in the subsample of central cities and cities with medium and low levels of economic development. This article proposes that SPA enterprises should reduce their carbon emissions and gradually explore a green and sustainable development path.